Multifunctional Structures - Sagara, Junko (World Bank, Washington, DC, 2013)
Public facilities and infrastructure can be built in such a way as to reduce disaster risks and serve as disaster risk management facilities. Roads, expressways, and other public facilities helped reduce damage and loss in the Great East Japan Earthquake (GEJE) by providing protection against flooding and by serving as evacuation routes and base stations for emergency operations. Organizations for disaster management and other public sector organizations should coordinate to ensure that their public works are multifunctional whenever possible; and cost-sharing mechanism should be developed to ensure that the financial burden is shared equitably. This report gives findings; lessons; and recommendations for developing countries.